Historical Geography of the Sinai Peninsula and its impact in the regional and international milieu - Bin Saleh, Yasmin Kamel Salim (Journal of Humanities & Social Sciences, 2020)
The research aimed to shed light on the Sinai peninsula and its importance throughout the ages, and its impact on the regional and international circles, and to reveal the manifestations of strength that lie behind the geographical location and historical role of Sinai. The study relied on the historical inductive approach, in addition to analyzing and evaluating the writings on the Sinai, with a view to arriving at general rulings on the strategic importance of the Sinai Peninsula through the ages. Geographic information systems. The research is based on a study of the historical geography of the Sinai Peninsula, its impact on the regional and international circles, and the revelation of the manifestations of strength that underlie Sinai’s geographical location and historical role. The study also dealt with the natural, human and economic ingredients that the Sinai Peninsula played a major role in its impact, as well as the study of the political borders and problems of Sinai, the extent of its impact on the Palestinian and Israeli sides, and the status of the Sinai Peninsula. The most important results: It became clear through the study the importance of the geographical location of the Sinai Peninsula, and the natural and human constituents helped to reinforce this importance, in addition to the strategic depth that it enjoys, as well as the area of ​​the peninsula that is not commensurate with the population, which led to the resettlement of the population by a state Arab Egypt, to be its first line of defense. The study recommended the necessity of accelerating the comprehensive and sustainable development of the Sinai Peninsula, and investing economic resources.